Climate change, fundamental interests, and global justice. Issue 5 (2nd September 2016) - Knight, Carl
Abstract : Political philosophers commonly tackle the issue of climate change by focusing on fundamental interests as a basis for human rights. This approach struggles, however, in cases where one set of fundamental interests requires one course of action, and another set of fundamental interests requires a contradictory course of action. This article advances an alternative response to climate change based on an account of global justice that gives weight to utilitarian, prioritarian, and luck egalitarian considerations. A practical application of this pluralistic account is provided, which shows that it handles trade-offs between individuals' interests in an appealing way and that it supports an aggressive policy of climate change mitigation. This account provides a more plausible justification for rights against the harms of climate change.